Lead-free high refractive index glasses produced from local raw materials - P. Dararutana (2018)
Many difference useful and decorative articles have been made from glasses over the centuries, especially lead-containing glasses. Due to harmful effects of lead from glass fabrication process on human beings and considering the health as well as the environmental issues, many researchers tried to produce leadless glasses using some heavy chemical elements such as barium, bismuth and zirconium. Nowadays, barium compounds seemed to be satisfactory and to be able to increase the refractive index. For production of high quality crystal glasses with high refractive index in Thailand, most raw materials including high quality sand have been imported. Because, Thailand, in fact, is rich in many kinds of raw materials for glass manufacturing, therefore, this work is set up to study the fabrication of the lead-free high refractive index glasses using local sand and barite as the main raw materials. After complete melting, the physical and optical properties of the prepared glass samples were determined to compare these properties with those of glasses prepared from foreign sand. It was found that the prepared glasses produced from local raw materials were suitably for restoration, decoration, radiation shielding, as well as glass jewelry. These glasses can be considered as one of the environmental friendly materials. © 2008 Trans Tech Publications.